2007
DOI: 10.1001/archpedi.161.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Travel by Walking Before and After School and Physical Activity Among Adolescent Girls

Abstract: Our results provide evidence that walking to and from school increases weekday minutes of total physical activity and MVPA for middle-school girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 28 publications
(33 reference statements)
7
85
3
Order By: Relevance
“…6 Our finding that active commuting to school was inversely related to obesity differs from previous studies that did not support this relationship. [23][24][25][26][27][28][29][30][31][32][33][34][35] Our large sample size provided more power to detect a relationship compared with smaller studies [23][24][25][26][27][28][29][30][31][32][33][34][35] and enabled us to examine relationships between active commuting and obesity, not just BMI or overweight/obesity. 31,33,34 Our result was only statistically significant after adjustments, indicating previous studies may not have detected the relationship because important covariates were not included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Our finding that active commuting to school was inversely related to obesity differs from previous studies that did not support this relationship. [23][24][25][26][27][28][29][30][31][32][33][34][35] Our large sample size provided more power to detect a relationship compared with smaller studies [23][24][25][26][27][28][29][30][31][32][33][34][35] and enabled us to examine relationships between active commuting and obesity, not just BMI or overweight/obesity. 31,33,34 Our result was only statistically significant after adjustments, indicating previous studies may not have detected the relationship because important covariates were not included.…”
Section: Discussionmentioning
confidence: 99%
“…21 Although there may be other benefits associated with active commuting to school, to date there is scant evidence that it reduces childhood obesity. 20,22 A systematic review of active commuting to school in elementary school children 23 revealed that active commuters were more physically active than their peers in 11 out of 13 studies, [24][25][26][27][28][29][30][31][32][33][34] but only 1 study revealed an inverse relationship with BMI. In that study, active commuting among fourth graders was associated with a lower BMI at baseline but did not significantly predict overweight/obesity at baseline or 2 years later.…”
mentioning
confidence: 99%
“…The corresponding values for the Philadelphia application of the LandScan model are 44.8% and 62.2%; therefore, our data are roughly representative of both the length and mode of school commuting for the nation as a whole. They are not representative, however, of other areas of the country participating in the Trial of Activity for Adolescent Girls (TAAG) study in which only 15% of students walked to school and 1% biked (Saksvig et al, 2007). The TAAG study, however, does not focus on urban areas and, therefore, probably, is not too relevant to the Philadelphia situation.…”
Section: Discussionmentioning
confidence: 99%
“…ATS can be an additional source of PA for school age youth [23][24][25][26][27]. Rates of PA participation, however, have declined over the past 20 years and, on average, less than 15% of schoolchildren regularly walk or bicycle to school [28].…”
Section: Discussionmentioning
confidence: 99%